THE INFLUENCE OF CHANGE AGENTS ON INFORMATION TECHNOLOGY DIFFUSION IN FIRMS - Hargo Utomo (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
The role of change agents in technological diffusion and innovation at firm level has been addressed in published literature mostly within the context of the developed countries. However, the involvement of change agents in the diffusion and adoption of IT-based innovations by small and medium-sized firms in the developing countries is largely unexplored. The main research questions are why and how management decisions to adopt and use IT are influenced (if any) by the interactions of key people in firms with several identified change agents. Case studies are used as the preferred approach to answer the research questions and to understand the qualitative aspects of IT diffusion at the level of the firm. The study concludes that IT diffusion in small and medium-sized firms expose mixed institutional influences. The mechanism by which change agents are involved in IT diffusion is also unique and is claimed to be different from that is generally found in other studies in this area. Some policy implications are proposed by this study.